Planar Characterization â€“ Graph Domination Graphs - Elakkiya, A.; Yamuna, M. (International Journal of Engineering and Technology, 2018)
In this paper, we characterize planarity and outer planarity of complement of graph domination graphs and provide a MATLAB program for identifying graph domination graphs.Â Â